Mapping Research Landscape on Ijarah Accounting: A Bibliometric Study Based on PSAK 107 Literature - Olivia, Hastuti; Saban, Azizah; Pulungan, Ja'far Hamzah; Maharanni, Nathasyah Putri; Tanjung, Nurdelima; Arip, Muhammad Abdul (AL-MUZARA'AH, 2025)
The development of ijarah accounting in Indonesia is in line with the growth of the Islamic financial sector which continues to show a positive trend. Compliance with the Statement of Financial Accounting Standards (PSAK), particularly PSAK 107 on Ijarah Accounting, is crucial in ensuring transparency and accountability of financial statements of Islamic financial institutions. However, although PSAK 107 has been in effect since 2010, in-depth and sustained academic studies on this topic are still limited, especially in the Indonesian context. To comprehensively explore the research on PSAK 107, a bibliometric review was conducted using Scopus and Crossref academic databases. ScienceDirect and Emerald Insight academic databases were used for data updates, covering the period 2014-2024 for Scopus and 2019-2024 for Crossref. Article metadata from Scopus and Crossref downloaded on April 17, 2024 were processed using BibTeX and RIS formats with R Studio and VOSviewer software. This collaborative study categorizes research themes on PSAK 107 using metadata from 1187 articles indexed in Scopus and Crossref between 2014 and 2024. The mapping visualization results show that the dominant themes are PSAK 107 and Ijarah, while topics such as Accounting, Ijarah Contracts, Ijarah Financing, and Islamic Profitability are identified as potential research opportunities. Another important finding is the dominance of contributions from Malaysia and Pakistan, with very little representation of research from Indonesia. This indicates a significant literature gap on the implementation and development of Ijarah accounting based on PSAK 107 in Indonesia. In addition, a number of topics such as Sukuk Ijarah, Accountability, and Ujrah are relatively under-researched, thus offering great room for further scientific exploration. Therefore, this study emphasizes the urgency for researchers in Indonesia to fill the literature gap to strengthen local understanding and contribute to the global discourse of Islamic accounting.